Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Hasil Belajar Matematika XI IPA 3 SMAN 10 Medan - Siti Rahmah; Haryati Ahda Nasution; Cut Latifah Zahari; Ummi Aulia; Yofita Ningtias (Journal on Education, 2024)
Class XI IPA 3 students at SMA Negeri 10 Medan will be using the TSTS cooperative learning paradigm to enhance their mathematical learning results. A total of thirty-two students participated in the research, which used Classroom Action Research (CAR). Conducted in two cycles, each cycle includes two sessions using the TSTS model and one session for evaluation. Data were collected through observations of teacher and student activities, as well as learning outcome tests. From the first to the second cycle, the findings demonstrate that both the teacher's and the students' actions significantly improve. During iteration two, teacher activity reached the "very good" category with an average score of 40 and a percentage of 90.90%. Student activity also improved to the "very good" category, with increased interest, attention, participation, and presentation. Student achievement significantly increased, with the average score rising from 77.34 in the first cycle to 86.56 in the second cycle. Another positive change was the increase in the percentage of students who reached mastery, which went from 65.625% to 93.75% between the two cycles. The implementation of the TSTS cooperative learning model has proven effective in enhancing student participation, interaction, and collaboration, as well as helping them better understand the subject matter.